Disaster Vulnerability Assessment of Low-Cost Houses in Java Island - Aulina Adamy; Meillyta Meillyta; Lisa Maharani; Faiza Aidina; Qurratul Aini (Journal of Contemporary Urban Affairs, 2023)
Among all of the Indonesian islands, Java poses the highest risk for all types of disasters, making it a significant threat to low-cost houses due to its high population vulnerability. The objective is to enhance comprehension of it by conducting a building typology analysis concerning various natural hazards/ risks. The methodology consists of 10 sample houses field observation, AutoCAD drawing, literature analysis, and built environment expert interviews. The results developed four categories of houses emphasising brick or timber walls with a combination of clay tile or zinc roofs. Related to disaster vulnerability, an improper building structure is the main problem. Smooth roof material is significant in a volcano eruption, a complete interconnection of structure is a must for the tornado, light materials are preferable in an earthquake zone, natural material is not recommended for high risk of forest fire, and elevating floor is mandatory in flooding. Focus on designing the four categories’ houses and quality control of the construction process are two strategies recommended. Also, a minimum of two types of disasters in the area should be considered in the design. Resilient low-cost houses will have an impact on reducing casualties, environmental damage, and economic losses. Covering more samples and areas in Java in future studies will provide a comprehensive understanding of low-cost houses.